2020
DOI: 10.1111/disa.12388
|View full text |Cite
|
Sign up to set email alerts
|

Building disaster resilience using social messaging networks: the WeChat community in Houston, Texas, during Hurricane Harvey

Abstract: Analyses of disaster resilience have focused increasingly on the role of social capital and online social networks in recovery. This study complements this field of work by investigating three key issues. First, it examines how a social messaging application, WeChat, helped individuals to access and to mobilise three types of social capital—bonding, bridging, and linking—during Hurricane Harvey, a Category 4 storm that made landfall in Louisiana and Texas in the United States in August 2017, resulting in signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Recent research has highlighted the significance of social media and ICTs for individuals’ and groups’ disaster communication (e.g. Chu & Yang, 2020; Houston, Hawthorne et al, 2015; Jurgens & Helsloot, 2018; Stephens et al., 2020). Extending this line of research, the present study shows that organizations’ capacity to engage stakeholders via two‐way social media communication and use of other types of ICTs to build external communication capacity have serious implications for improving organizational DRR performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has highlighted the significance of social media and ICTs for individuals’ and groups’ disaster communication (e.g. Chu & Yang, 2020; Houston, Hawthorne et al, 2015; Jurgens & Helsloot, 2018; Stephens et al., 2020). Extending this line of research, the present study shows that organizations’ capacity to engage stakeholders via two‐way social media communication and use of other types of ICTs to build external communication capacity have serious implications for improving organizational DRR performance.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study highlights external communication capacity (Shumate et al., 2017) as a particular type of nonprofit capacity that shapes organizational communication processes and performance. Third, this research contributes to a growing body of research on the role of ICTs, particularly social media, in disaster organizing (Chu & Yang, 2020; Houston, Spialek et al, 2015; Rajput et al, 2020; Stephens et al., 2020). Finally, this research enriches a communication‐centred view of interorganizational collaboration (e.g.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The congruence between the different definitions of community resilience is that communities must possess certain capacities that must lead to adaptation. In this regard, four primary sets of adaptive capacities are essential for building community resilience, that is (1) economic development (level of economic resources, degree of quality in the distribution of resources and the scale of diversity in economic resources), (2) social capital (social support, social participation and community bonds), (3) information and communication (systems and infrastructure for informing communities, communication and narratives) and (4) community competence (collective action and decision-making, collective efficacy and empowerment) (Chu & Yang 2020 ; Norris et al 2008 ; Sherrieb, Norris & Galea 2010 ). These adaptive capacities provide a roadmap for enhancing community resilience to disasters (Norris et al 2008 ).…”
Section: Collaboration For Building Community Resilience: Conceptual Justificationmentioning
confidence: 99%
“…Algorithms have been developed to identify flood victims asking for help on Twitter [ 17 ]. Going beyond publicly available social media, research have found that private SMS messaging groups have been integral to the spread of information among small communities during hurricanes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%